Implementação de medidas ergonômicas em uma indústria calçadista: uma análise de suas influências sobre as condições de trabalho na atividade de desenformar calçados - Colaço, Geraldo Alves (2013)
This work has the analyzing aim, the influence of ergonomic implementation measures at the job conditions of the cemented mounting sector in the activity of unmolding shoes in an industry at Paraíba State. Therefore, we make a comparative analysis according to the ergonomic improvings, previously established at the company job sections according to the methodology situation, problem and improving (SPI), trying to discover if the application of these actions influenced or not the job conditions at the cemented mounting sector. We discuss about a relevant subject, due to the ascertainment in the strong growing of the footwear industry in Brazil northeast region which has a great variety of gathered activities in its productive process. However, historically, this kind of industry does not have in their functioning ways an ergonomic accident prevention culture. Consequently we may see the elevation of the disease quantity related to the working in this sector, due to the productive process complexity, the working organization or the equipment little offering that guide to the reduction or the elimination struggle by the worker, which, in some cases, occurs on his body or in the mental limits. In the methodological procedures, we did some semi- structured interviews with the workers of the industry mounting sector, trying to do the measurement of the working conditions through the methodologies application: Situation, Problem and improving (SPI), using the tools Occupational Repetitive Action (OCRA), Gravity, Urgency and Tendency (GUT) and the aching area diagram. As a result, it is observed an improving in the working conditions with the activity nonergonomic conditions elimination, besides when we enable more motivation, better life quality, among the employees of the studied sector.